Decolonize this art history: Imagining a decolonial art history programme at Kalamazoo College (UCL Press, 2021)
This article presents a case study of a decolonized curriculum development in the Art History programme at the small liberal arts institution Kalamazoo College (Michigan, USA). It discusses the curriculum plan, methods for learning, assessment and potential applications for this approach beyond the case study. Paying attention to questions about the origins of art history, and its long-established methods and canon within the Western academy, this article proposes that any approach to decolonizing an art history curriculum must take into account the frameworks and methods of the knowledge systems it employs, must continually assess, reflect and hold accountable those who participate in its implementation and maintenance, and, importantly, must recognize that decolonization work is a necessarily messy and ongoing process.